The application of correction factors on serum retinol of Indonesia school children (Medical Journal of Indonesia, 2010)
Aim: Vitamin A deficiency among children is still a public health problem in Indonesia. Serum/plasma retinol concentration is the best indicator in assessing vitamin A status. However, there is growing concern that infection/ inflammation lowers serum  retinol concentration, thus creating potential misinterpretation of vitamin A status, which could affect policy makers in planning suitable nutrition programs targeted at community. The aim of this study was to highlight the importance of applying correction factors, to better interpret serum retinol as a nutritional statusbiomarker.Methods: A cross sectional study involving 54 apparently healthy school children was conducted in East Nusa Tenggara. Height, body weight, concentrations of serum retinol, CRP and AGP were assessed. Based on concentrations of serum CRP and AGP, four infl ammation groups were determined, namely reference,  incubation, early convalescence and late convalescence groups. Correction factor was obtained by dividing serum retinol  concentration of reference group by that of the other three groups. Correction factors were then used to correct serum retinol concentration without any  influence of infection/ inflammation.Results: The prevalence of stunting and underweight were 43% and 22% respectively, but there was no wasting among the school children. Applying correction factor lowered the prevalence of vitamin A defi ciency from 20.4% to 18.5%; thus changing vitamin A defi ciency from a severe public health problem to a moderate public health problem.Conclusion: Correcting serum retinol concentration for the infl uence of infection reduced the apparent severity of vitamin A deficiency. This could affect policy for planning nutrition programs designed for communities. (Med J Indones 2010;  19:258-63)Keywords: correction factor, infection, school children, serum retinol